Improving child and parenting outcomes following paediatric acquired brain injury: a randomised controlled trial of Stepping Stones Triple P plus Acceptance and Commitment Therapy. (17th March 2014) - Brown, Felicity L.; Whittingham, Koa; Boyd, Roslyn N.; McKinlay, Lynne; Sofronoff, Kate
<x xml:space="preserve">Abstract</x> Background Persistent behavioural difficulties are common following paediatric acquired brain injury (ABI). Parents and families also experience heightened stress, psychological symptoms and burden, and there is evidence of a reciprocal relationship between parent and child functioning, which may be mediated by the adoption of maladaptive parenting practices. Despite this, there is currently a paucity of research in family interventions in this population. The aim of this study was to determine the efficacy of Stepping Stones Triple P: Positive Parenting Program (SSTP), with an Acceptance and Commitment Therapy (ACT) workshop, in improving child outcomes and parenting practices following paediatric ABI. Methods Fifty‐nine parents of children (mean age 7 years, SD 3 years, 1 month; 35 males, 24 females) with ABI (Traumatic injuries 58%, Tumour 17%, Encephalitis or meningitis 15%, Cardiovascular accident 7%, Hypoxia 3%) who were evidencing at least mild behaviour problems were randomly assigned to treatment or care‐as‐usual conditions over 10 weeks. Mixed‐model repeated‐measures linear regression analyses were conducted to compare conditions from pre‐ to postintervention on child behavioural and emotional functioning (Eyberg Child Behavior Inventory, Strengths and Difficulties Questionnaire) and dysfunctional parenting style (Parenting Scale). Assessment of maintenance of change was conducted at a 6‐month follow‐up. The trial was registered on Australian New Zealand Clinical Trials Registry (ID: ACTRN12610001051033, www.anzctr.org.au). Results Significant time‐by‐condition interactions were identified on number and intensity of child behaviour problems, child emotional symptoms and parenting laxness and overreactivity, indicating significant improvements in the treatment condition, with medium‐to‐large effect sizes. Most improvements were maintained at 6 months. Conclusions Group parenting interventions incorporating Triple P and ACT may be efficacious in improving child and parenting outcomes following paediatric ABI.